Internal audit efficiency evaluation principles - Savčuk, Olga (Journal of Business Economics and Management, 2007)
Current business environment has experienced rapid and revolutionary change with far reaching consequences for companies worldwide. Management responses to fierce global competition include improved quality and risk management initiatives, reengineered structures and processes and greater accountability to ensure more timely, reliable and relevant information for decision‐making and to secure confidence and trust of the investors. Over the last few years the importance to the strong corporate governance of managing risk has been increasingly acknowledged. Companies are under pressure to identify all the business risks they face: social, ethical and environmental as well as financial and operational, and to explain how they manage them to an acceptable level. Therefore in order to reach its objectives each company has to develop and implement an approach to assessing and managing the uncertainties and opportunities it faces in the pursuit of its business strategy, with the intention of maximizing shareholder value and performance, i.e. meeting the determined objectives. Shareholders are extremely demanding with respect to the activities of the management and want an independent and objective assessment of the risk management and governance system the management is responsible for. In this radically changed business environment the internal auditing gained an important role within companies. Over the past sixty years internal audit developed from control function responsible for inspection of accounting and financial data to a strategic partner for the shareholders and the management of the company in improving governance processes. In current environment the management of the company more and more rely on the internal audit to evaluate whether controls are sufficient to manage risks and uncertainties. This developing role of the internal auditing is also reflected in its current definition, i.e. internal auditing is an independent, objective assurance and consulting activity designed to add value and improve a company's operations. It helps an organization accomplish its objectives by bringing a systematic, disciplined approach to evaluate and improve the effectiveness of risk management, control and governance processes. Only efficient internal audit can perform its tasks properly. Internal audit efficiency depends on its subordination level, which must be appropriate for internal audit to be independent and objective, on the professional qualification and practical experience of internal audit staff, on the internal audit strategy, activities and value added to the company and on the ability to improve itself. The article analyses efficient internal audit establishment and support issues and internal audit efficiency estimation principles. Taking into account the scope of organization's direction and control, internal audit takes on important roles, integrating several other governance and control aspects into organizational governance and stands out as the most important, single mechanism for ensuring adequate and effective governance of the organization. The article provides criteria to assess efficiency of internal audit which could be applied when implementing internal audit function or improving the existing one.First Published Online: 14 Oct 2010